指状锥面二次包络圆柱蜗杆传动接触线分析 - 彭晓南; 王自兴 (Jixie chuandong)
Based on differential geometry and spatial engaging theory,a set of formula of finger conical surface double enveloping worm gearing is derived.Through an example,the undercutting boundary line and contact line are depicted.At the same time,the variation law of the lubricating angle and the inductive normal curvature is analysed.